A practical study on direct PCR amplification using the GlobalFiler™ PCR Amplification Kit on human bloodstains collected with microFLOQ™ Direct swabs. (July 2019) - Chong, Kevin Wai Yin; Wong, Yongxun; Ng, Boon Kiat; Lim, Wei Siong Holden; Rosli, Afiqah Razanah; Syn, Christopher Kiu Choong
Highlights: Targeted sample collection using microFLOQ™ Direct swabs requires minimal handling. Direct PCR amplifications using microFLOQ™ Direct swabs can be used for urgent casework. DNA results obtained within 3 h from submission for direct amplification. Direct PCR amplifications is usable for bloodstains on common casework samples. PCR additives improve peak heights and peak height balance in STR-DNA profile. Abstract: Rapid DNA profiling of casework samples is a powerful tool that can support law enforcement agencies in the quick apprehension of perpetrators before they re-offend or escape the jurisdiction. This present study evaluated the feasibility of direct PCR amplification, using the microFLOQ™ Direct swab, for generating DNA profiles (from bloodstains) within 3 h. The swab tip is coated with nylon fibers pre-treated with cell lysing agent, which allows for the direct PCR amplification of collected samples without DNA extraction and quantification, thereby shortening the time required to obtain a DNA profile. Samples collected were directly amplified using GlobalFiler™ PCR Amplification Kit with and without the presence of a PCR additive. Addition of the PCR additive enhanced the peak heights of DNA profiles by approximately 2 fold. Hence, an additive could improve results obtained in the absence of a DNA purification step, especially since casework samples may contain PCR inhibitors. Subsequently, these swabs, amplified using the GlobalFiler™ PCR Amplification Kit with PCR additive, were evaluated on common substrates encountered in routine casework samples submitted with bloodstains, such as denim jeans, knife blade, tissue paper, leather belt, shirt, and blood swabs. The minimum peak heights observed were generally above the analytical and stochastic thresholds established by the laboratory. Finally, the microFLOQ™ Direct swab workflow was compared to the laboratory's standard workflow of DNA profiling comprising of conventional processing steps such as extraction using the DNA-IQ™ chemistry on Maxwell ® 16, followed by quantification, amplification and capillary electrophoresis. The average peak heights of the DNA profiles generated by direct PCR amplification were similar or exceeded those generated using the standard workflow. This study clearly demonstrates that direct PCR amplification using microFLOQ™ Direct swab can be used in a rapid workflow to obtain DNA profiles from casework samples.